Teaching English reading using local wisdom-based media and material at MTs Mu’allimat NWDI Pancor - Risviana; Siti Maysurah; M. Junaidi Marzuki (Journal of English Language Proficiency, 2026)
This study aims to explore the impact of using local wisdom-based media and materials in English reading instruction at MTs Mu’allimat NWDI Pancor. Employing a mixed-methods approach with a sequential explanatory design, this research allows the researcher not only to measure the effect of local wisdom-based materials on students’ reading skills but also to explore their responses and motivation throughout the learning process. In the quantitative phase, a pre-experimental design with a one-group pretest-posttest model was used to assess the improvement in students’ reading comprehension before and after the intervention. Meanwhile, in the qualitative phase, semi-structured interviews were conducted to investigate students’ perceptions and motivation regarding the use of local wisdom-based materials. The interview data were analyzed using thematic analysis based on Miles and Huberman’s (1994) framework. The participants of this study consisted of 30 eighth-grade students selected through purposive sampling.The findings indicated a significant improvement in students’ reading comprehension after the implementation of local wisdom-based materials, as shown by the increased post-test scores. Furthermore, the qualitative data revealed that students felt more motivated and engaged when learning through texts that reflected their own culture and personal experiences. The integration of local wisdom was proven to enhance cognitive understanding and foster emotional connection, thereby supporting the development of reading skills. These findings suggest that culturally relevant materials can serve as an effective pedagogical strategy to improve both reading comprehension and learning motivation among junior high school students.